Usage of alkaline glucose for Synthesis Copper Nano particle on Polyester Fabric - Jolaei, Mohammad Mahdi; Montazer, Majid; Rashidi, Abo-Saeed; Moghadam, Mohammad Bameni (Ciência e Natura, 2015)
In this study, Nano copper from the chemical reaction between copper salt and sodium hydroxide was produced. Interestingly, simultaneous synthesis of Nano-copper chemical method and depositing Nano materials on the fabric’s surface. The glucose is used as a stabilizer. An important feature of this study is, simplicity, availability, low cost and etc. The results create Nano-copper with a thickness of 30-40 nanometers on the surface of the fabric is shown. The treated fabrics could be used in diverse areas such as defense, aerospace, electronics, medical and health industries.